Imaging of Fetal Orbits - Mirsky, David; Feygin, Tamara (Journal of Pediatric Neuroradiology, 2015)
Abnormalities of the fetal orbit are occasionally visualized in the workup of suspected central nervous system malformation. It may be difficult to recognize orbital pathology in fetuses, especially when it is bilateral and symmetric. In this article, we at first addressed a normal appearance of the fetal orbits on prenatal imaging, which includes obstetric ultrasound and fetal magnetic resonance imaging. We also described a spectrum of lesions involving fetal eyes and orbits, including abnormal fetal orbital biometry, abnormal morphology of the vitreous and lens, and neoplastic and nonneoplastic masses of the orbits. Fetal orbital anomalies may be associated with a long list of underlying systemic disorders. For that reason, sometimes a particular orbital anomaly may be helpful as a denominator to narrow a diagnosis. Detection of fetal orbital lesions should prompt a diligent search for associated birth defects arising at the same time or sharing the same progenitor cell.
Keywords: fetal orbits; biometry; coloboma; cataract; microphthalmia; MRI; US